2022
DOI: 10.3389/fpsyg.2022.885606
|View full text |Cite
|
Sign up to set email alerts
|

One Year on: The Impact of COVID-19 on the Lives of Freelance Orchestral Musicians in the United Kingdom

Abstract: Before the drastic disruption caused by the sudden emergence of the COVID-19 pandemic, 85% of the United Kingdom’s 14,000 orchestral musicians were self-employed freelance workers, engaged in busy and varied portfolio careers comprising a combination of orchestral, West End theatre, chamber music, and commercial recording work. Between May and June 2020 we carried out a first study examining the impact of the pandemic on the lives of 24 self-employed orchestral musicians, all established freelancers. Twelve we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…One of the professional coping strategies identified by the participants was maintaining their playing skills through regular practice and learning to play new instruments. Similarly, Cohen and Ginsborg (2021, 2022) reported motivation to play, practice, and expand musical skills as sub-themes in their analysis of interviews of professional orchestral musicians. Fram et al (2021) also reported that some musicians explored new ways of being collaborative and expanded their practices during the pandemic, following an initial period of acute loss.…”
Section: Findings and Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…One of the professional coping strategies identified by the participants was maintaining their playing skills through regular practice and learning to play new instruments. Similarly, Cohen and Ginsborg (2021, 2022) reported motivation to play, practice, and expand musical skills as sub-themes in their analysis of interviews of professional orchestral musicians. Fram et al (2021) also reported that some musicians explored new ways of being collaborative and expanded their practices during the pandemic, following an initial period of acute loss.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…As Mahdiani and Ungar (2021) explain, “exposure to significant threat or severe adversity and the achievement of positive adaptation are consistent attributes of resilience” (p. 148). Similarly, Cohen and Ginsborg (2022) reported post-traumatic growth in mid-career musicians who were “open to new possibilities” and “discovering personal strengths” post-pandemic (pp. 10–11).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations